If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying (s + -5)(s + 3) = 0 Reorder the terms: (-5 + s)(s + 3) = 0 Reorder the terms: (-5 + s)(3 + s) = 0 Multiply (-5 + s) * (3 + s) (-5(3 + s) + s(3 + s)) = 0 ((3 * -5 + s * -5) + s(3 + s)) = 0 ((-15 + -5s) + s(3 + s)) = 0 (-15 + -5s + (3 * s + s * s)) = 0 (-15 + -5s + (3s + s2)) = 0 Combine like terms: -5s + 3s = -2s (-15 + -2s + s2) = 0 Solving -15 + -2s + s2 = 0 Solving for variable 's'. Factor a trinomial. (-3 + -1s)(5 + -1s) = 0Subproblem 1
Set the factor '(-3 + -1s)' equal to zero and attempt to solve: Simplifying -3 + -1s = 0 Solving -3 + -1s = 0 Move all terms containing s to the left, all other terms to the right. Add '3' to each side of the equation. -3 + 3 + -1s = 0 + 3 Combine like terms: -3 + 3 = 0 0 + -1s = 0 + 3 -1s = 0 + 3 Combine like terms: 0 + 3 = 3 -1s = 3 Divide each side by '-1'. s = -3 Simplifying s = -3Subproblem 2
Set the factor '(5 + -1s)' equal to zero and attempt to solve: Simplifying 5 + -1s = 0 Solving 5 + -1s = 0 Move all terms containing s to the left, all other terms to the right. Add '-5' to each side of the equation. 5 + -5 + -1s = 0 + -5 Combine like terms: 5 + -5 = 0 0 + -1s = 0 + -5 -1s = 0 + -5 Combine like terms: 0 + -5 = -5 -1s = -5 Divide each side by '-1'. s = 5 Simplifying s = 5Solution
s = {-3, 5}
| 125000+65.00x=0 | | 8x^2+8x-16=0 | | x/-31.8=-349.8 | | 4x^2-9y^2+40x-36y-8=0 | | 2x^2+16x+33=0 | | -4x-12-6x=10 | | 2/64=4/x | | 35=-3x+5 | | 4.1x+51.8*8=9.5-10.0 | | 5u+9=1 | | 3(3x-4)=20-(6x-10) | | log^3(x+6)=2 | | 9t^2-18t=0 | | 3n+6m-8=3m+m | | 3z=2 | | Y=6ln(12x) | | 3x+15=60-6x | | 7(-3x+8)-50=-8(-3x-9) | | x-(.15x)=350 | | 81=1/n^4 | | 8x-3=21-3x+x | | T=6D+7cm | | 2085000000+5550000x=25000000 | | 7x-(2x+50)=7 | | 17(1/17) | | A=(2x-6)(3x-5) | | 2(4-a)=6a | | -8s=472 | | 8x^2+18x+3=0 | | c-508=291 | | (5x-7)+(4x)=110 | | j+2=52 |